Usulan Perbaikan Kualitas Menggunakan Pendekatan QCC dan AHP pada Produk Heat Exchanger di PT. Tokki Engineering and Fabrication - M. Fariq Alfawwaz; Hendi Iskandar; Indra Gumelar (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
Tokki Engineering and Fabrication is a company engaged in the fabrication of industrial equipment such as heat exchangers. During the period from January to March 2025, the company produced three units of heat exchangers, all of which were identified to have weld joint defects based on radiography inspection results. A total of 34 out of 315 films were rejected, with porosity being the dominant defect type, accounting for 21 cases or 62%. The approach used was the Quality Control Circle method, supported by analysis tools such as fishbone diagrams, matrix diagrams, and solution selection using the Analytical Hierarchy Process. The study results indicate that the use of blowers in the welding area is the main root cause of porosity defects. Among four evaluated alternative solutions, installing visual signs and warning indicators in the work area was chosen as the most effective and preventive improvement proposal. If this improvement is implemented, the defect rate is estimated to decrease by 100%, based on assessments by internal company experts who understand the actual processes and conditions in the field. Keywords: AHP, Heat Exchanger, Matrix Diagram, Porosity Defect, Quality Control Circle